Canine Thyroid Cancer: Molecular Characterization and Cell Line Growth in Nude Mice. Issue 2 (March 2020) - Hassan, Bardes B.; Altstadt, Lucas A.; Dirksen, Wessel P.; Elshafae, Said M.; Rosol, Thomas J.
Thyroid cancer is the most common endocrine malignancy in dogs. Dogs and humans are similar in the spontaneous development of thyroid cancer and metastasis to lungs; however, thyroid cancer has a higher incidence of metastasis in dogs. This study developed a preclinical nude mouse model of canine thyroid cancer using a canine thyroid adenocarcinoma cell line (CTAC) and measured the expression of important invasion and metastasis genes in spontaneous canine thyroid carcinomas and CTAC cells. CTAC cells were examined by electron microscopy. Short tandem repeat analysis was performed for both the original neoplasm and CTAC cells. CTAC cells were transduced with luciferase and injected subcutaneously and into the tail vein. Tumors and metastases were monitored using bioluminescent imaging and confirmed with gross necropsy and histopathology. Invasion and metastasis genes were characterized in 8 follicular thyroid carcinomas (FTCs), 4 C-cell thyroid carcinomas, 3 normal thyroids, and CTAC cells. CTAC cells grew well as xenografts in the subcutis, and they resembled the primary neoplasm. Metastasis to the kidney and lung occurred infrequently following subcutaneous and tail vein injection of CTAC cells. STR analysis confirmed that CTAC cells were derived from the original neoplasm and were of canine origin. Finally, 24 genes were differentially expressed in spontaneous canine thyroid carcinomas, CTAC, and normal thyroids. This study demonstrated the usefulness of a nude mouse model of experimental canine thyroid carcinoma and identified potential molecular targets of canine follicular and C-cell thyroid carcinoma.